Organizaciones de la sociedad civil y la “securitización” de la migración internacional indocumentada en México - Treviño Rangel, Javier (El Colegio de México A.C., 2016)
Undocumented international migration in Mexico is facing a serious human rights crisis. Each year, hundreds of thousands of migrants, above all from Central America, cross Mexico to reach theUnited States. Their journey risks extortion, kidnap, torture, disappearance,and death. For activists and civil society bodies, thiscrisis is explained by what they call the “securitization” of migrationpolicy. By “securitization” they understand a policy imposedon Mexico by the United States that treats migrants as a security threat. This paper challenges this interpretation, arguing that the theory of securitization is insufficient to understand the many factors that make possible the systematic violence of the human rights of migrants in transit.